Therapeutic Intra-arterial Hyaluronidase Infusion for Ophthalmic Artery Occlusion Following Cosmetic Facial Filler (Hyaluronic Acid) Injection*. (February 2014) - Oh, Baek-Lok; Jung, Cheolkyu; Park, Kyu Hyung; Hong, Young Jae; Woo, Se Joon
Abstract Although dermal/subcutaneous injection of filler into the face is a popular aesthetic surgery, severe complications related to arterial occlusion, including skin necrosis and visual loss, have been reported. Herein, we report a case of intra-arterial hyaluronidase infusion in the ophthalmic artery and other arteries supplying the facial skin following hyaluronic acid injection at the glabella and nasal ala. Despite direct hyaluronidase infusion into the ophthalmic artery, retinal arterial perfusion was not restored, but branches of the ophthalmic and facial arteries were recanalised. Skin discoloration was normalised, and partial recovery of retinal and choroidal perfusion and complete recovery of ocular movement were achieved.